2022
DOI: 10.1002/acr2.11436
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiome in Patients With Dermatomyositis

Abstract: Objective The study objective was to compare the microbial composition of patients with dermatomyositis (DM) and healthy controls (HCs) and determine whether microbial alterations are associated with clinical manifestations of DM. Methods The 16S ribosomal RNA gene sequencing was performed on fecal samples from patients with DM and HCs. Microbial composition and diversity were compared between subjects with DM and HCs and in association with several DM‐specific clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Beyond the phylum level, they were also more abundant in Streptococcus, Lachnoclostridium, and Tyzzerella 3 and 4 while less abundant in Bifidobacterium, Christensenellaceae R-7 group and Anaerostipes compared to the health controls. However, the researcher indicated that these differences were not significantly associated with the DM diseases [10]. Overall, the difference observed between DM patients and health control microbiota at the phylum level does indicate some correlation of microbiota dysbiosis and the develop of DM, although the result does not provide a strong support for the difference at the genus level.…”
Section: Dermatomyositis (Dm)mentioning
confidence: 89%
“…Beyond the phylum level, they were also more abundant in Streptococcus, Lachnoclostridium, and Tyzzerella 3 and 4 while less abundant in Bifidobacterium, Christensenellaceae R-7 group and Anaerostipes compared to the health controls. However, the researcher indicated that these differences were not significantly associated with the DM diseases [10]. Overall, the difference observed between DM patients and health control microbiota at the phylum level does indicate some correlation of microbiota dysbiosis and the develop of DM, although the result does not provide a strong support for the difference at the genus level.…”
Section: Dermatomyositis (Dm)mentioning
confidence: 89%
“…Previous research reported that patients with dermatomyositis had lower microbial diversity compared with healthy controls. Results from alpha and beta diversity showed a clear difference in the bacterial richness and community between IIM patients and healthy controls ( 24 ). However, our results were not entirely consistent with some researches.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome has also been implicated in dermatomyositis (DM), an autoimmune myopathy associated with muscle weakness and skin rashes. DM patients were reported to have lower gut microbial diversity compared with healthy controls [ 81 ], and a subgroup of DM patients with interstitial lung disease (ILD)-associated MSA had decreased abundance of Christensenellaceae and Ruminococcaceae . There are only limited data on the role of the skin microbiota in rheumatoid autoimmune disorders such as SLE, and further studies are warranted to identify and elucidate the function of specific skin microbial species in the cutaneous manifestations of patients with rheumatoid disorders.…”
Section: Lessons From Other Rheumatic Disorders—the Role Of Microbiotamentioning
confidence: 99%